The Uber of the underworld. (Economist, 2025)
The article shows how a network of young hackers are using plug-and-play hacking kits and ransomware subscriptions to take down computer systems of multinational companies. It provides an overview of the business models used by hackers who develop rasomware and steal data used to commit fraud. It discusses criminals' use of information-stealing malware that infects computers and smartphones, as well as artificial intelligence (AI) to produce malware and conduct phishing attacks.